Providing a model of purchase intention and customer experience on customer behavior in virtual networks - Kazem Tolooee; Hossein budaghi Khajeh Noubar; Hossein Gharehbiglo; Mojtaba Ramazani (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe purpose of this research is to provide a model of purchase intention and experience of customer on customer behavior in virtual networks. The current research is applicable in terms of purpose, and descriptive-survey in terms of nature and method. The statistical population of the present study includes the customers of the stores of Afogh Korosh who bought from these stores in 2022 during one month (June), which was considered to be 384 people using Cochran's formula. Sampling is random, and a multi-stage cluster type. The collection tool in this research includes a questionnaire of purchase intention pattern based on customers' experience in designed virtual networks. Data analysis was done through SPSS and SMART PLS software. The effect of mindfulness and customer experience (respect for the customer, importance of time, banking operation research, customer value culture, modern technology, offering facilities, enjoyment, queuing system, environment coloring, and excellent situation) on the satisfaction, loyalty and trust of customers was proved. The results showed that the aspects of purchase intention and customer experience through effecting on customer behavior leads to better understanding of mindfulness and experimental factors among banking systems, and can increase satisfaction, loyalty and also trust among customers of Afogh Korosh store. Also, the research model has a good fit.Extended Abstract                                           IntroductionWith the powerful development of the Internet, web and mobile applications; customers get a wide range of options to choose their desired products and services (Duarte et al, 2018). Meanwhile, one of the emerging aspects, especially in our country, in this field is the emergence of online stores (Rasuli et al, 2018). Maintaining a high level of online shopping convenience has become a strategic driving force for online retailers to promote and maintain customer loyalty (Duarte et al, 2018). Despite the many advantages of online stores that have been mentioned, the problem here is that when a customer visits and intends to buy from an online store, he is not faced with a real seller and a real store, but with an online website and virtual store that presents information about his product and invites the customer to buy these products (Rasuli et al, 2018). An online marketplace focuses on capturing the needs of specific consumers and offers various possibilities for online retailers to advertise their products or services. To maintain a presence in the market, customer needs must be precisely understood. This understanding helps the market to improve service quality, trust and customer engagement to increase customer satisfaction and encourage the desire to buy more. (Putri et al, 2023). Practitioners need to better understand the factors that improve the relationship between consumers and online retailers, and increase revenue and profits. Increasing competition in the market has forced businesses to develop a stronger relationship with their customers, which positively affects their repurchase decisions (Antwi, 2021). Therefore, the researcher is trying to answer the question: how does the presentation of the model of purchase intention and customer experience affect the behavior of customers in virtual networks?Theoretical FrameworkIntention to buyRepurchase intention refers to the repeat purchase of a particular brand by a customer after using the same brand, or the customer's belief in continuing to buy from a particular company in the future (Bulut, 2015). Customer experience Chen & Yang (2021) in their research define customer experience as the dominance of online customers on customer interactions and the environment of service employees, policies and sales processes, in which the higher the customer experience, the greater the increase in business performance in e-commerce. (Anifa, 2022).Customer Satisfaction Mirzaee Azandariani & Arya (2022) define satisfaction as follows: Customers' reaction to evaluate the perceived difference between prior expectations or to some extent ideal performance and the actual performance of the product, which is perceived after consumption. Customer satisfaction is defined as the result of an effective evaluation of a benchmark compared to perceived performance in practice. In other words, if the perceived performance meets expectations, satisfaction has been achieved (Shahab Far, 2017).Customer loyaltyLoyalty is a strong deep commitment created for stable and continuous repurchase of a preferred product or service in the future, while there are situational influences and competitors' marketing efforts to change the customer's use towards another product or service (Wolter et al. et al., 2017).Customer trustTrust refers to all the skills that customers have and all the decisions made by customers to achieve a goal (Aziziyah, 2020).Kim & Park (2023) conducted a research on the influence of virtual influencers' attractiveness on purchase intention: a product moderated mediation model. The findings showed that the attractiveness of virtual influencers is not directly related to purchase intention. However, imitative desire and brand attachment mediated this relationship. In addition, the conditional direct effect of virtual influencers' attractiveness on purchase intention was partially supported while the indirect effects were moderated by imitative desire and brand attachment by product-endorser fit.Tang (2023) conducted a research on empowering digital marketing with interactive virtual reality in interior design: effects on customer satisfaction and behavioral intention. The results showed that the above factors positively affect customer satisfaction with a digital platform empowered by the internal design of the IVR. It was found that the quality of information has the greatest impact among these three factors. Although many researchers have conducted in-depth research on digital marketing, existing research lacks a consumer perspective to examine the factors that most influence consumers. In addition, relatively little work has been done to determine customer perceptions of a digital marketing approach using virtual interior design and its interactive features. Therefore, a theoretical model for interactive virtual interior design features for digital marketing is proposed.Research methodologyThe current research is applicable in terms of purpose and descriptive-survey in terms of nature and method. The statistical population of the present study includes the customers of the stores of Afogh Korosh who bought from these stores in 2022 during one month (June), which was considered to be 384 people using Cochran's formula. Sampling is random, a multi-stage cluster type. The collection tool in this research includes a questionnaire of purchase intention pattern based on customers' experience in virtual networks.Research findingsData analysis was done through SPSS and SMART PLS software. The effect of mindfulness and customer experience (respect for the customer, importance of time, banking operation research, customer value culture, modern technology, offering facilities, enjoyment, queuing system, environment coloring and excellent location) on the satisfaction, loyalty and trust of customers was approved. The results showed that the dimensions of purchase intention and customer experience with the effect on customer behavior on better understanding of mindfulness and experimental factors among banking systems can increase satisfaction, loyalty and also trust among customers of Afogh Korosh store. Also, the research model of It has a good fit.ConclusionThe current research has been conducted with the aim of providing a model of purchase intention and customer experience on customer behavior in virtual networks. The results of this research are aligned with the results of Kim & Park (2023), Tang (2023), Rusta et al, (2023), Kautish et al, (2023), Asgari & Naghdi (2021), Kosa & Uysal (2021), Boak (2021), Golalizadeh et al, (2023), Poursalimi & Bayat (2022), Pakrovan et al, (2022), Torkrar et al, (2022), Kazemi et al, (2021). Tang (2023) showed that the above factors positively affect customer satisfaction with a digital platform empowered by the internal design of the IVR. It was found that the quality of information has the greatest impact among these three factors. Although many researchers have conducted in-depth research on digital marketing, existing researches lack a consumer perspective to examine the factors that most influence consumers. In addition, relatively little work has been done to determine customer perceptions of a digital marketing approach using virtual interior design and its interactive features. Therefore, a theoretical model for interactive virtual interior design features for digital marketing is proposed.According to the results of the research, the following suggestions are presented:1- Increasing electronic services on the store's website and application in order to create more satisfaction and motivation in customers and repeat purchases.2- Creating this mentality in customers that they will have more benefit to buy from this store; this will cause the frequency of purchases in customers and increase customer satisfaction.3- Increasing the benefit perceived by the customer in order to their better understanding about the store's products and also creating satisfaction and loyalty in them.